1985
DOI: 10.1007/bf03348509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on PRL secretion during different photoperiods of the day in prepubertal and pubertal healthy subjects

Abstract: The effect of melatonin on PRL secretion has not been established yet. In an attempt to establish whether PRL response to melatonin changes in relation to the photoperiods of the day and pubertal maturation, we evaluated PRL plasma levels after melatonin administration in 19 prepubertal and pubertal healthy subjects of both sexes in two different periods of the day: in the morning, when the sensitivity to melatonin is low, and in the afternoon, when the responsiveness to melatonin is higher. Melatonin was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Treatment with agomelatine was also associated with a short‐term and modest elevation of PRL levels that occurred within 1 h following the agonist administration. This observation is consistent with previous studies on the effects of exogenous melatonin administration 40,41,44,46–48 . The mechanisms are still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with agomelatine was also associated with a short‐term and modest elevation of PRL levels that occurred within 1 h following the agonist administration. This observation is consistent with previous studies on the effects of exogenous melatonin administration 40,41,44,46–48 . The mechanisms are still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…The stimulation of prolactin was evident after melatonin administration in both the morning and the evening, but with an enhancement of the response in the evening. Two recently published studies [Mauri et al, 1985;Lissoni et al, 19861 also observed a stimulation of prolactin after acute injection of melatonin in postpubertal subjects, although the response was only observed during the afternoon and not during the morning. These studies did not report the concentrations of melatonin in the peripheral circulation, after melatonin injection; therefore, there may have been a difference in the concentratiotls of melatonin achieved in the two study periods.…”
Section: Discussionmentioning
confidence: 89%
“…The only exception was the study by Carman et al [109], discussed earlier, in which very high melatonin doses were administered. In the literature more broadly, isolated studies have raised concerns about a number of more serious AEs, including increased seizure frequency or severity or new onset seizures [81], delayed puberty [143,144], reproductive dysfunction [145,146], insulin resistance [87,89] and other endocrine effects [77,84,145,[147][148][149][150][151][152][153][154][155][156][157] and asthma symptoms [5,158,159]. The evidence for these effects is, in the majority of cases, based on findings from a single study or a very small number of studies and remains controversial.…”
Section: Placebo-controlled Studiesmentioning
confidence: 99%